Some Games in áº›- PRE- g- separation axioms - B., Esmaeel R.; Jassam, Ahmed A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2021)
The primary purpose of this subject is to define new games in ideal spaces via set. The relationships between games that provided and the winning and losing strategy for any player were elucidated.